Configurational Prediction of CYP2A6 Substrate Would Guide the Screening of Potential Substrate (Journal of Atomic and Molecular Sciences, 2019)
Cytochrome P450 2A6 (CYP2A6) substrate database constitute a potential class of disease relatedmolecules as well as therapeutic molecules, primarily expressed in liver and lungs. The prediction of CYP2A6-related metabolism is of great interest. In this study, a docking protocol was presented which made use ofposes of known substrate to help guide the configurational search and to rank predicted poses of testsubstrates. As a result, a 68% success rate was obtained. Predicting ideal configurations of compound wouldmake significant impact on screening potential substrate, as the predicted bound conformations of 3Tanshinone IIa (CYP2A6 substrate) analogues revealed differences among them and the inappropriatecharacteristic to be selected as substrates which was confirmed experimently.